Electricity for the entertainment electrician & technician - Cadena, Richard (Focal Press, 2014)
"Electricity for the Entertainment Electrician & Technician reinforces the fundamentals of electricity, power distribution, and safety, and explains the latest developments in technology for the live entertainment technician. The application of electricity for the theatre or a concert stage is not the same as for a residence or commercial building, and this is the only reference on the market that explains what live entertainment technicians need to know and why. Written by an ETCP (Entertainment Technician Certification Program) trainer, this reference supports practicing technicians and provides new technicians the assistance needed for a successful career in the entertainment industry. The second edition will be fully updated with new information on systems, protocols, regulations, and safety standards, and will now be in full color. The author is also planning on including more international material and more practice problems at the end of each chapter. The author will be hosting a companion website with extra resources, including conversion tables, voltage spreadsheets, articles from Lighting & Sound International, Lighting & Sound America, and Protocol, and animations and illustrations depicting electricity and electric power distribution developed for his workshops."